Studies on the Antidiabetic and Antinephritic Activities of Paecilomyces hepiali Water Extract in Diet-Streptozotocin-Induced Diabetic Sprague Dawley Rats. (29th February 2016) - Wang, Juan; Teng, Lirong; Liu, Yange; Hu, Wenji; Chen, Wenqi; Hu, Xi; Wang, Yingwu; Wang, Di
Abstract : Paecilomyces hepiali is a fungus widely used in Asian countries for various potential pharmacological activities. The present study aims to evaluate the antidiabetic and antinephritic effects of the Paecilomyces hepiali mycelium water extract (PHC) in diabetic rat, which is established by eight-week high-fat diet administration followed by one-week tail intravenous injection of 25 mg/kg streptozotocin (STZ). After four-week 0.12 g/kg metformin and PHC at doses of 0.08, 0.4, and 2.0 g/kg treatment, an increment of body weight, a decrement of plasma glucose, low levels of total cholesterol, and low density lipoprotein cholesterol in diabetic rats were observed. PHC promotes glucose metabolism by enhancing insulin, pyruvate kinase activity, and increasing the synthesis of glycogen. PHC normalized the disturbed levels of superoxide dismutase, methane dicarboxylic aldehyde, and glutathione peroxidase in kidney. The inhibitory effects on the levels of interleukin-2, interleukin-6, interleukin-10, and tumor necrosis factor-α in serum and kidney revealed the protection of PHC against diabetic nephropathy. Compared with nontreated diabetic rats, four-week PHC treatment resulted in a decrement on nuclear factor kappa B expression in kidney. These results show that Paecilomyces hepiali possesses antidiabetic and antinephritic effects which are related to the modulation of nuclear factor kappa B activity.